2014
DOI: 10.1016/j.celrep.2014.03.075
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Targeting of CoREST Controls Polarization of Migrating Cortical Neurons

Abstract: The migration of cortical projection neurons is a multistep process characterized by dynamic cell shape remodeling. The molecular basis of these changes remains elusive, and the present work describes how microRNAs (miRNAs) control neuronal polarization during radial migration. We show that miR-22 and miR-124 are expressed in the cortical wall where they target components of the CoREST/REST transcriptional repressor complex, thereby regulating doublecortin transcription in migrating neurons. This molecular pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 64 publications
2
67
0
Order By: Relevance
“…During cortex development in rat, for example, a bipolarto-multipolar transformation of neural progenitor cells occurs when they reach the intermediate zone; another transformation -back to a bipolar morphology -is required for the subsequent glia-guided locomotion of these cells in the cortical plate (Noctor et al, 2004). Notably, Dicer1 deletion at this stage inhibits the conversion of neurons from a multipolar to a bipolar shape during migration (Volvert et al, 2014), suggesting an involvement of miRNAs in neuronal polarization (Fig. 2C).…”
Section: Neuronal Polarization Axon Pathfinding and Dendritogenesismentioning
confidence: 96%
See 2 more Smart Citations
“…During cortex development in rat, for example, a bipolarto-multipolar transformation of neural progenitor cells occurs when they reach the intermediate zone; another transformation -back to a bipolar morphology -is required for the subsequent glia-guided locomotion of these cells in the cortical plate (Noctor et al, 2004). Notably, Dicer1 deletion at this stage inhibits the conversion of neurons from a multipolar to a bipolar shape during migration (Volvert et al, 2014), suggesting an involvement of miRNAs in neuronal polarization (Fig. 2C).…”
Section: Neuronal Polarization Axon Pathfinding and Dendritogenesismentioning
confidence: 96%
“…in the case of miR-134; Gaughwin et al, 2011) or indirectly by targeting members of the CoREST/REST transcriptional repressor complex (e.g. in the case of miR-22 and miR-124; Volvert et al, 2014). In these studies, elevated levels of miR-134, miR-22 or miR-124 attenuated neuronal migration by downregulating Dcx expression.…”
Section: Migrationmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, when analyzed at E14.5, projection neurons migrate radially predominantly via locomotion on radial glia cell (RGC) fibers. This locomotion of projection neurons along RGC fibers requires a more stable morphology that mostly involves MT regulation by its associated proteins [15,56,57]. In contrast, interneurons migrate tangentially, mostly relying on actomyosin dynamics to support nucleokinesis, dynamic branching of their leading process [10,11,53,58] and their direction of migration [59].…”
Section: Multiple Roles For Elongator During the Establishment Of Thementioning
confidence: 99%
“…[24][25][26] It was previously shown that neuronal migration defects can affect the multipolar-bipolar transition of cortical neurons which is important for correct placement of these cells within the cortex. 27 Due to the finding that miR-338 has the capacity to influence the migration of neurons toward the CP, we examined whether modulation of miR-338 expression alters the morphology of neurons within the CP.…”
Section: Mir-338 Affects Neuronal Morphologies and Polarity In Vivomentioning
confidence: 99%